2010
DOI: 10.1086/653001
|View full text |Cite
|
Sign up to set email alerts
|

Positive Allometry and the Prehistory of Sexual Selection

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: The function of the exaggerated structures that adorn many fossil vertebrates remains largely unresolved. One recurrent hypothesis is that these elaborated traits ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 42 publications
4
59
1
Order By: Relevance
“…The lack of overwhelming support for any particular model is likely due to the short time series. An increase in body size in Permo-Carboniferous non-mammalian synapsids has been qualitatively noted since specimens were first placed in a stratigraphic context (Romer and Price 1940;Olson 1962;Gould 1967;Pivorunas 1970;Gould and Littlejohn 1973;Bakker 1986;Tracy et al 1986;Berman et al 2001;Tomkins et al 2010;Reisz and Fröbisch 2014;Brink et al , 2015. Reisz and Fröbisch (2014) proposed that a trend towards increased body size can be observed in all herbivorous lineages, and also posited a body size increase in the Sphenacodontidae; although they suggested that this increase was less than that observed in herbivores.…”
Section: Time Series Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of overwhelming support for any particular model is likely due to the short time series. An increase in body size in Permo-Carboniferous non-mammalian synapsids has been qualitatively noted since specimens were first placed in a stratigraphic context (Romer and Price 1940;Olson 1962;Gould 1967;Pivorunas 1970;Gould and Littlejohn 1973;Bakker 1986;Tracy et al 1986;Berman et al 2001;Tomkins et al 2010;Reisz and Fröbisch 2014;Brink et al , 2015. Reisz and Fröbisch (2014) proposed that a trend towards increased body size can be observed in all herbivorous lineages, and also posited a body size increase in the Sphenacodontidae; although they suggested that this increase was less than that observed in herbivores.…”
Section: Time Series Analysismentioning
confidence: 99%
“…Sphenacomorpha is the only group of medium-to-large bodied non-mammalian synapsids to have developed elongate neural spines forming a dorsal sail, the function of which has been subject to intense scrutiny (Romer 1927;Rodbard 1949;Pivorunas 1970;Bramwell and Felqett 1973;Haack 1986;Tracy et al 1986;Bennett 1996;Florides et al 2001;Huttenlocker et al 2010Huttenlocker et al , 2011Tomkins et al 2010;Rega et al 2012). It has been suggested that sphenacomorphs were the largest terrestrial vertebrates of the Permo-Carboniferous because of their dorsal sails, as the sail would act to strengthen the vertebral column at large body masses and increase the efficiency of thermoregulation (Romer 1927;Pivorunas 1970;Florides et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What matters is that there was significant variation within Pteranodon sternbergi. Additionally, if the cranial crests of Pteranodon were sexually dimorphic (Bennett 1992;Tomkins et al 2010;Hone et al 2012;Knell et al 2013), then they were probably under the influence of sexual selection. In modern animals, sexually selected or "signal" traits are more variable than those of non-signal traits, with respect to their size, shape, colour, and presence/absence (e.g., Alatalo et al 1988;Wiens 2001;Cuervo and Møller 2009;Tazzyman and Iwasa 2010;Emlen et al 2012).…”
mentioning
confidence: 99%
“…However, there is no direct association of the skulls and pelves that could back this hypothesis (e.g., Kellner and Tomida 2000). Furthermore, it has been suggested that, at least theoretically, the differences found by Bennett (1992) could be accounted for ontogeny and taxonomy (Tomkins et al 2010). In fact, a re-evaluation of several specimens attributed to Pteranodon has shown that in some cases there are sufficient morphological differences other than the shape and size of the cranial crest, supporting a larger taxonomic diversity within what can be called the Pteranodon-complex (Kellner 2010).…”
Section: Discussionmentioning
confidence: 98%